Biodegradable polymeric micelles encapsulated JK184 suppress tumor growth through inhibiting Hedgehog signaling pathway1. Issue 6 (14th February 2015) - Zhang, Nannan; Liu, Shichang; Wang, Ning; Deng, Senyi; Song, Linjiang; Wu, Qinjie; Liu, Lei; Su, Weijun; Wei, Yuquan; Xie, Yongmei; Gong, Changyang
<x xml:space="preserve">Abstract</x> For developing aqueous formulation and improving anti-tumor activity of JK184, we prepared JK184 encapsulated MPEG-PCL micelles which showed a stronger inhibition of Gli expression in Hh signaling in pancreatic carcinoma.